The Ethiopian Food System Country Profile - Chege, Christine Gacheri Kiria; Lundy, Mark M.; Béné, Christophe (2022)
The Ethiopian Food System Country Profile: Global and national economy; Macro, mesoand local shocks and stresses (e.g. conflict); Culture, social norms; Political economy